2023
DOI: 10.1021/jacsau.3c00011
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reactivity of Polyoxometalates toward Proteins: From Interactions to Mechanistic Insights

Abstract: The latest advances in the study of the reactivity of metal-oxo clusters toward proteins showcase how fundamental insights obtained so far open new opportunities in biotechnology and medicine. In this Perspective, these studies are discussed through the lens of the reactivity of a family of soluble anionic metal-oxo nanoclusters known as polyoxometalates (POMs). POMs act as catalysts in a wide range of reactions with several different types of biomolecules and have promising therapeutic applications due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 137 publications
0
31
0
Order By: Relevance
“…Furthermore, it should be noted that the presence of biomolecules in solution can impact the stability and behavior of POMs (50,51). In particular, POM-protein and POM-peptide interactions are complex and important areas of research that must be considered in many biological applications (52)(53)(54). These interactions can influence the efficacy and specificity of POMs in various biological contexts, making their study of great importance in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be noted that the presence of biomolecules in solution can impact the stability and behavior of POMs (50,51). In particular, POM-protein and POM-peptide interactions are complex and important areas of research that must be considered in many biological applications (52)(53)(54). These interactions can influence the efficacy and specificity of POMs in various biological contexts, making their study of great importance in the field.…”
Section: Discussionmentioning
confidence: 99%
“…M-POMs with highly Lewis acidic metal centers, such as Ce 4 + , Zr 4 + and Hf 4 + , have been shown to effectively and selectively hydrolyze peptide bonds in a diverse range of proteins and, interestingly, the nature of embedded metal center has been observed to have an influence on the selectivity of the hydrolysis. [4,20,[57][58][59] The proposed mechanism involves activation of the carbonyl group in the peptide bond through coordination of the embedded Lewis acid metal center to the carbonyl oxygen. [20,60] This proposed mechanism is supported by the observed coordination of a Zr 4 + -substituted Keggin POM to the carbonyl group of an asparagine residue (Asn65) in a cocrystal of the POM with HEWL (Figure 3d).…”
Section: Types Of Pom-protein Interactionsmentioning
confidence: 99%
“…Although crystallographic and computational studies have shown that the embedded metal center in M‐POMs most likely does not play a major role in POM‐protein interactions, further studies have revealed the importance of the nature of the incorporated metal centers on POM reactivity towards proteins. M‐POMs with highly Lewis acidic metal centers, such as Ce 4+ , Zr 4+ and Hf 4+ , have been shown to effectively and selectively hydrolyze peptide bonds in a diverse range of proteins and, interestingly, the nature of embedded metal center has been observed to have an influence on the selectivity of the hydrolysis [4, 20, 57–59] . The proposed mechanism involves activation of the carbonyl group in the peptide bond through coordination of the embedded Lewis acid metal center to the carbonyl oxygen [20, 60] .…”
Section: Types Of Pom‐protein Interactionsmentioning
confidence: 99%
See 2 more Smart Citations